Monte Carlo Study of XSO4 (X= Ba, Be, Ca, Mg, and Sr) Response to Common Particles (Proton, Electron, and Neutron): A Shielding Application - Güldal, Serkan (Fırat University, 2020)
Subatomic particles are continuously studied by researchers parallel to developing detectors and theories. In experiments, accelerated particles penetrate the considered target and even shielding. Thus, the protection of researchers and equipment from high energy particles is an important problem in the field of high energy physics. Because of the need, researchers are looking for new materials to be used for shielding (besides detectors, dosimeters, and many other applications). In this study, we have tested the interaction of proton, electron, and neutron for various energy levels with XSO4 (X= Ba, Be, Ca, Mg, and Sr) targets. XSO4 is in the powder structure, so it is mobile unlike concrete. We show the energy deposition of particles in the defined geometry. The simulation results show MgSO4 is significantly less responsive to proton and neutron beams. Thus, it is less likely a shielding material between the considered molecules. The other important conclusion, the most of the proton beams energy is absorbed by the listed molecules show similar responsiveness as concrete which makes these molecules possible alternatives as a shielding material in the high energy experiments.

Detektörlerdeki ve teorilerdeki gelişmelere paralel olarak atom altı parçacıklar çalışılmaya devam edilmektedir. Deneylerde hızlandırılmış parçacıklar çalışılan hedeflerin ve hatta zırh içine bile nüfuz etmektedir. Bu sebepten dolayı araştırmacıları ve ekipmanları yüksek enerjili parçacıklardan korumak yüksek enerji araştırmalarında önemli bir problemdir. Bu ihtiyaçtan dolayı, araştırmacılar (detektör, dozimetre, ve diğer uygulamaların yanı sıra) zırh olarak kullanılabilecek yeni malzemeler arayışındadır. Bu çalışmada proton, elektron ve nötron ışınlarına maruz bıraktığımız XSO4 (X= Ba, Be, Ca, Mg, ve Sr) moleküllerini çeşitli enerji seviyeleri için inceledik. XSO4 pudra yapısındadır, böylece betonun aksine taşınabilirdir. Tanımlanan geometride enerji dağılımları incelendi. Yapılan analizler gösterdi ki MgSO4 diğer moleküllere kıyasla proton ve nötron ışınımlarına belirgin bir şekilde daha az tepki göstermiştir. Diğer bir önemli sonuç ise proton ışınımın enerjisinin büyük bir kısmı analiz konusu olan moleküller tarafından tutulmuştur, bu davranış referans noktası olarak kullandığımız beton ile benzerlikler göstermesi deney düzeneklerinde bu moleküllerin alternatif zırh malzemesi olarak kullanılabileceğini düşündürmektedir
XSO4 (X= Ba, Be, Ca, Mg, ve Sr)’ün Bilinen Parçacıklara (Proton, Elektron, ve Nötron)Tepkisinin Monte Carlo Çalışması: Bir Zırh Uygulaması